Bis[2-amino-6-methyl-pyrimidin-4(1H)-one-κN,O]dichloridocadmium(II) - Kaabi, Kamel (2010)
In the title compound, [CdCl(2)(C(5)H(7)N(3)O)(2)], the Cd(II) atom is six-coordinated by two heterocyclic N atoms [Cd-N = 2.261 (2) and 2.286 (2) Å] and two O atoms [Cd-O = 2.624 (2) and 2.692 (2) Å] from two bidentate chelate 2-amino-6-methyl-pyrimidin-4(1H)-one ligands and two chloride ions [Cd-Cl = 2.4674 (6) and 2.4893 (7) Å]. The crystal packing is characterized by an open-framework architecture with the crystal packing stabilized by inter-molecular N-H⋯Cl and N-H⋯O hydrogen bonds.